Medication access: Policy and practice opportunities for pharmacists. Issue 1 (27th December 2020) - Sobeski, Linda M.; Schumacher, Christine A.; Alvarez, Nancy A.; Anderson, Keri C.; Bradley, Bridget; Crowe, Susie J.; Merlo, Jessica R.; Nyame, Adwoa; Rivera, Kelley S.; Shapiro, Nancy L.; Spencer, Dustin D.; Van Dril, Elizabeth
Abstract: Medication access is critical to achieving optimal patient outcomes. The 2020 Task Force on Medication Access was charged with developing an ACCP white paper on improving medication access that addresses barriers such as cost, health disparities, and utilization management practices. This white paper outlines major barriers to medication access and provides pharmacists and professional organizations with policy and practice recommendations to help reduce barriers, enhance medication access, and fulfill the goal of optimal patient outcomes.